2012
DOI: 10.1353/hpu.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in HIV-treatment Responses between Haitians, African Americans, and Hispanics Living in Miami-Dade County, Florida

Abstract: Haitians are not doing as well on HAART as other groups. This may be explained by linguistic, cultural, or other barriers that are not currently addressed by the health care system in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although HIV is now a treatable chronic disease, Haitians are less likely than other groups to succeed in HIV treatment and often experience suboptimal outcomes (Colasanti et al, 2012). Due to the stigmatization of both HIV and cancer in the Haitian community, existing barriers to cervical cancer screening are likely compounded for Haitian women living with HIV (Kobetz et al, 2009; Saint-Jean, Metsch, & Gomez-Marin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although HIV is now a treatable chronic disease, Haitians are less likely than other groups to succeed in HIV treatment and often experience suboptimal outcomes (Colasanti et al, 2012). Due to the stigmatization of both HIV and cancer in the Haitian community, existing barriers to cervical cancer screening are likely compounded for Haitian women living with HIV (Kobetz et al, 2009; Saint-Jean, Metsch, & Gomez-Marin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our clinic serves a diverse minority Black population ranging from African Americans to immigrant women from Haiti, Jamaica, and other Caribbean islands. Haitians account for one of the largest foreign-born Black populations diagnosed with HIV/AIDS in the United States 26 and are less likely to achieve viral suppression compared with African Americans and Hispanics after receiving cART 27 . The Haitian population carries a higher burden of HPV, with a prevalence as high as 20.7%, with oncogenic strains (13.2% of the total Haitian population) accounting for most of these infections 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Haitians account for one of the largest foreign-born Black populations diagnosed with HIV/AIDS in the United States 26 and are less likely to achieve viral suppression compared with African Americans and Hispanics after receiving cART. 27 The Haitian population carries a higher burden of HPV, with a prevalence as high as 20.7%, with oncogenic strains (13.2% of the total Haitian population) accounting for most of these infections. 28 As a result, the Haitian population experiences a high rate of cervical cancer, occurring in 38/100,000 women, 4 times higher than the rate in the general Florida population.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to HIV, there have been delays in HIV diagnosis among Haitians [ 29 ]. Haitians were also noted to have disparities in treatment responses for HIV [ 30 , 31 ]. In addition, studies have shown that Haitian women are more likely to be diagnosed with late-stage breast cancer and low compliance with annual mammograms [ 32 , 33 ].…”
Section: Health Disparities Among Haitiansmentioning
confidence: 99%